1985
DOI: 10.1149/1.2114305
|View full text |Cite
|
Sign up to set email alerts
|

Tri‐ and Tetravalent Phthalocyanine Thin Film Photoelectrodes: Comparison with Other Metal and Demetallated Phthalocyanine Systems

Abstract: A series of trivalent and tetravalent metal phthalocyanines (Pc) has been examined in thin film form on metal substrates by electron microscopy, UV-visible spectrophotometry, and electrochemical and photoelectrochemical techniques. These Pc's are compared with other divalent metal and demetallated phthalocyanines. The tri-and tetravalent phthalocyanines show enhanced photoresponses vs. the divalent metal and demetallated systems. This enhanced activity correlates with their broadened and red-shifted visible sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 49 publications
0
22
0
2
Order By: Relevance
“…In many cases, it has been found that the Q band is very sensitive to the environment of the molecule, and is also more sensitive to changes in the number and the orientation of nearest neighbor phthalocyanines in the solid state [35]. For main group elements, such as the Al and Ga [36], the filled 4d orbitals are below the filled p ring levels and the unfilled 4s orbitals are above the p* orbitals. Thus, the central metal does not directly participate in the electronic transition.…”
Section: Uvevis Spectroscopymentioning
confidence: 99%
“…In many cases, it has been found that the Q band is very sensitive to the environment of the molecule, and is also more sensitive to changes in the number and the orientation of nearest neighbor phthalocyanines in the solid state [35]. For main group elements, such as the Al and Ga [36], the filled 4d orbitals are below the filled p ring levels and the unfilled 4s orbitals are above the p* orbitals. Thus, the central metal does not directly participate in the electronic transition.…”
Section: Uvevis Spectroscopymentioning
confidence: 99%
“…[16,17] Many of the tri-and tetravalent metal phthalocyanines (in comparison to phthalocyanines of divalent metals and unsubstituted phthalocyanines) show a superior photoresponse. [18] It was ascribed due to structural differences in the cofacial stacking of the Pc rings, and results in enhanced electrical contact with the conductive substrate. Previous photoelectrochemical investigations on thin films of Pcs have described that tetravalent-metal Pc, Vanadyl Pc (VOPc) showed good photovoltaic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among molecular materials manifesting sensitivity to added impurities, phthalocyanine (Pc) thin films are particularly interesting because of their chemical and thermal stability, ease of preparation and compatibility with vacuum deposition, and their light absorbing properties in the visible and nearinfrared region (9). Photoelectrochemical studies performed on thin films of trivalent and tetravalent metal Pc's (10)(11)(12)(13) have demonstrated that these materials can have reasonable energy conversion efficiencies (14,15) and that the contrast between dark conductivity (adk) and photoconductivity (crph) is higher in these films (as much as 1000:1) (10)(11)(12)(13)(14)(15)(16)(17)(18) than in the more commonly studied divalent metal Pc's (2:1 at most). The effect of added or adventitious impurities on these electrical properties has been noted, and particularly, the open-circuit photovoltages appeared to be affected by impurities collected at an interface with the organic material (8,11,19).…”
Section: Introductionmentioning
confidence: 99%